1957
DOI: 10.1002/jctb.5010071004
|View full text |Cite
|
Sign up to set email alerts
|

New calcium aluminate hydrates

Abstract: Several modifications of the ‘hexagonal’ tetracalcium and dicalcium aluminate hydrates have been obtained, some of which have not been described previously. Only a newly established 4CaO,Al2O3, 19H2O hydrate, and an α‐form and a hitherto undescribed β‐form of a 2CaO,Al2O3,8H2O hydrate have been found to occur in the aqueous system at 25°. Other modifications are produced on drying under various conditions. The 4CaO,Al2O3,19H2O hydrate, characterized in the X‐ray patterns by a longest basal spacing of 10·6Å, is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

1963
1963
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 2 publications
0
10
0
2
Order By: Relevance
“…During hydration of the CAC‐Ceramic‐Composite material after 6 hours the C 2 AH 7.5 content suddenly rises on the expense of C 2 AH 8.2 and C 2 AH 8 . It is reported that C 2 AH 7.5 is formed by drying C 2 AH 8 at 34% relative humidity . At the same time the CA 2 hydration stops (see Figure ).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…During hydration of the CAC‐Ceramic‐Composite material after 6 hours the C 2 AH 7.5 content suddenly rises on the expense of C 2 AH 8.2 and C 2 AH 8 . It is reported that C 2 AH 7.5 is formed by drying C 2 AH 8 at 34% relative humidity . At the same time the CA 2 hydration stops (see Figure ).…”
Section: Discussionmentioning
confidence: 93%
“…(microcrystalline AH 3 ) . In this temperature range the H 2 O content of the C 2 AH 8 phase varies between 7.5 and 8.2 moles during the hydration of calcium aluminates . Scheller and Kuzel determined space groups and lattice parameters for the 8‐, 7.5‐, and 5‐hydrates.…”
Section: Introductionmentioning
confidence: 99%
“…El aluminato de calcio hidratado formado depende de la temperatura y de la composición de la solución ya que la cantidad de agua interlaminar depende de la presión de vapor de agua y de la humedad de los hidratos que son fácilmente atacados por el CO 2 de la atmósfera (4)(5)(6) Simultáneamente tiene lugar una disminución de la intensidad del CaAl 2 O 4 , que indica otro hecho importante expuesto en la literatura, que podría estar asociado, a la ruptura de la capa hidroxílica formada principalmente por geles de AH x y pequeños cristalitos de hidratos que han crecido durante este intervalo de tiempo en la superficie de las partículas del CaAl 2 O 4 (25). La ruptura de esta capa, permite el acceso de agua al interior de los granos anhidros presentes en la pasta, para formar una nueva capa de productos amorfos, que se vuelve a romper a ~ 29 h, donde se observa de nuevo un aumento de la intensidad de la fase Ca 2 (27).…”
Section: Estudio En "Tiempo Real" De La Hidratación De Caal 2 Ounclassified
“…Taylor (56) states that before 1957, the compound now described as C^AH^g was considered to be C4AH13. Roberts (51) found that dehydration of C^AH^g to give C^AH-^ occurs very easily, as soon as the solid has been separated from its mother liquor.…”
Section: Calcium Aluminates X-ray Analysis and Electron Microscopymentioning
confidence: 99%
“…Roberts (51), Buttler, Classer and Taylor (10) and Aruja (4) have contributed in recent years to clarification of aluminate phases by x-ray and electron diffraction studies of single crystals.…”
Section: Calcium Aluminates X-ray Analysis and Electron Microscopymentioning
confidence: 99%